CSN: The Conceptually Manageable Sensor Network - Woojin Joe; Jonghyun Lee; Karpjoo Jeong (International Journal of Distributed Sensor Networks)
For the last decade, computer science and information technology have been rapidly expanding their application areas from computation and data processing inside computers to the real time monitoring and management of the real world outside computers. For those emerging applications such as Internet of Things, the flexible, scalable, and interoperable, collaborating sensor networks are crucial. In this paper, we present a sensor network system called the conceptually manageable sensor network (CSN). CSN is intended to support the conceptual management and integration of sensor networks and to provide well-defined and logical APIs for the facilitation of application development. The CSN design is based on the simple and intuitive conceptual model: sets and message queues. In order to minimize the system development efforts and to inherit the system quality of production level open source software, the CSN system is intentionally implemented as a set of extensions to the open source messaging system called ActiveMQ. We conducted some preliminary usability and performance tests for the current CSN implementation. For the usability test, we used data sets from a real world project for the energy-efficient management of Indoor Air Quality in subway stations. Both usability and performance tests showed promising results.